O planejamento e sistematização das dimensões conceitual, procedimental e atitudinal nas aulas de educação física: uma experiência através do Sport Education Model - Vargas, Tairone Girardon de (2018)
School Physical Education, throughout its history, has been recognized as an exclusively practical activity influenced by health, military institution and sport. From the 80's, the renovating movement sought to legitimize the area as a curricular component, stating that it possessed knowledge that was beyond simple to do, since it contained contents, even conceptual ones. Curricular proposals have been discussed in the perspective that Physical Education should be developed in such a way as to contemplate three dimensions of content: conceptual, procedural and attitudinal. However, teachers have shown difficulties in developing their classes in this perspective. In this sense, this research seeks to investigate the development of the conceptual, procedural and attitudinal dimensions in Physical Education classes in a public school in the northwestern state of Rio Grande do Sul through an experience with Sport Education Model. The work characterized by being an action research consisted in developing together with a collaborating teacher a cyclical process of planning, action, observation and reflection. The instruments used were: participant observation, which developed, from the planning accompaniment and Physical Education classes during the didactic unit of Gaucho Dances in a second-year high school class; the semi-structured interview with the teacher, who discussed the difficulties and potentialities of using the Sport Education Model to articulate the three dimensions of content; and focus group with the students, to evaluate the development of the didactic unit. The data were analyzed based on the triangulation of the information obtained with the three instruments. From this, we present the results describing six characteristics that define Sport Education (sports season, membership, internal competition, statistical record, festivity and culminating event), analyzing how the content dimensions were articulated in each of them. Thus, from the study, we can interpret that the experience of the Sport Education Model contributes to the articulation of the three dimensions of content in the course of a didactic unit; also gave opportunities to the students collaborating in the research to develop a cultured competence about the knowledge worked, a useful knowledge, and, mainly, an enthusiasm on the part of the students in the course of the classes. Therefore, the articulation of the three dimensions of content through the Sport Education Model contributes to the recognition of Physical Education as a curricular component composed of different corporal practices present in the diverse manifestations of the body culture of movement.